Factors influencing the use of genetic information for insurance risk assessment - Arych, Mykhailo (My University, 2025)
У статті досліджено особливості та роль генетичної інформації для оцінки страхових ризиків на ринку страхування життя в Україні. В Україні наразі існують певні ризики: по-перше, генетична дискримінація, адже більшість компаній страхування життя цікавляться генетичною інформацією страхувальників, можуть запитувати її у них та будь-яких інших третіх сторін, а тому існує ймовірність її використання для оцінки страхових ризиків; по-друге, інформаційна асиметрія, що є наслідком кращої поінформованості страхувальників про їхні страхові ризики, ніж страховиків. The article examines the speciﬁcs and role of genetic information for insurance risk assessment in the life insurance market in Ukraine. The results show that currently some risks exist in Ukraine: ﬁrstly, the genetic discrimination, since most life insurance companies are interested in the genetic information of policyholders, and can request it from any third parties: therefore, there is a possibility of using it to assess insurance risk; secondly, an information asymmetry, which is a consequence of greater awareness of insurance companies about the insurance risks than that of the policyholders. After all, policyholders may not inform the insurance company about all the genetic data (for example, the results of genetic studies) that describe their genetic predisposition to future changes in health.
Keywords: кафедра маркетингу; медичне страхування; страховий ризик; генетичні дані людини; health insurance; insurance risk; human genetic data